Molecular Events Occurring in Lipophagy and Its Regulation in Flaviviridae Infection - Wu, Keke; Fan, Shuangqi; Zou, Linke; Zhao, Feifan; Ma, Shengming; Fan, Jindai; Li, Xiaowen; Zhao, Mingqiu; Yan, Huichao; Chen, Jinding (Frontiers in Microbiology, 2021)
Diseases caused by Flaviviridae have a wide global and economic impact due to high morbidity and mortality. Flaviviridae infection usually leads to severe, acute or chronic diseases, such as liver injury and liver cancer resulting from hepatitis C virus (HCV) infection, dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS) caused by dengue virus (DENV). However, the pathogenesis of Flaviviridae infection is very complex and still not fully understood. Mounting evidence indicates that host autophagy is subverted to modulate the life cycles of Flaviviridae. Organelle-specific autophagy, one of the major subtypes of autophagy, selectively targets different organelles for quality control, which is essential for regulating cellular homeostasis. As an important sub process of autophagy, which is able to target lipid droplets (LDs) to regulate lipid metabolism, lipophagy is also closely related to the infection of a variety of pathogenic microorganisms. In this review, we briefly understand the LDs interaction relationship with Flaviviridae infection, outline the molecular events of how lipophagy occurs and the related research progress on the regulatory mechanisms of lipophagy in Flaviviridae infection. Exploring the crosstalk between viral infection and lipophagy induced molecular events may provide new avenues for antiviral therapy.